Compact Bi-EDF-Based Brillouin Erbium Fiber Laser Operating at the 1560-nm Region - Harun, Sulaiman Wadi; Parvizi, Roghaieh; Shahi, Sharifeh; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2009)
A single-frequency Brillouin erbium fiber laser (BEFL) is demonstrated operating at the 1560-nm region using a simple ring resonator with a very short piece of bismuthbased erbium-doped fiber (Bi-EDF) for the first time. A 49-cm-long Bi-EDF is used to provide both nonlinear gain and linear gain to generate a stimulated Brillouin scattering (SBS) and to amplify the generated SBS, respectively. The BEFL operates at 1559.49 nm with a peak power of -4 dBm and a side-mode suppression ratio of 14 dB when the Brillouin pump (BP) and 1480-nm pump powers are fixed at 6 dBm and 144 mW, respectively. The BP wavelength is also tunable within a wavelength range from 1558.8 to 1560.0 nm.